Isolasi dan Karakterisasi Fungi Pyricularia oryzae Penyebab Penyakit Blast pada Tanaman Padi - Astriawati, Fitri; Anfa, Qurrotul (Biospecies, 2025)
Blast disease caused by the fungus Pyricularia oryzae is one of the major diseases in rice plants (Oryza sativa) that can significantly reduce crop yields. This research aims to isolate and characterize P. oryzae macroscopically and microscopically. This study is exploratory research. The research methods include sampling leaves and stems of rice plants showing blast symptoms, isolating the fungus from infected plant tissues, and characterizing the macroscopic and microscopic features of the isolated fungi. The results showed that P. oryzae grown on PDA medium has colonies that are round with smooth edges, a velvety surface texture, light gray to dark gray with a blackish center, and white to gray concentric ring-like margins. Microscopically, the fungi P. oryzae produce asexual spores known as conidia that are pyriform in shape with two septa dividing the conidia into three cells. The conidia are attached to the tips or branches of conidiophores. The conidiophores of P. oryzae are transparent to brownish, tubular, long filaments, septate, and thicker at the base. This identification provides important information for more effective control of blast disease and the development of sustainable disease management strategies